TRADISI MEGIBUNG SEBAGAI STRATEGI ADAPTASI MASYARAKAT KAMPUNG ISLAM KEPAON DENPASAR BALI - Afifah, Zumrotul; Punia, I Nengah; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT The megibung tradition that still survives in Kepaon Islamic Village until now is one of the hard works of society in Kepaon Islamic Village for maintaining the megibung tradition. All components of society contribute hand in hand to preserve traditions that are increasingly eroded by the process of modernization. All components of society both from historical observers, mosque administrators to adolescents work together so that the Megibung tradition remains sustainable. Collaboration between these society components results in the solidarity of the society in Kepaon Islamic Village. Society relations are increasingly close, especially with the existence of megibung. Megibung has more impact on introducing the unknown and closer to the familiar. Keywords; Megibung Tradition, Strategy of Adaptation, Moslem Society of Kepaon Denpasar